An amorphous LiO2-based Li-O2 battery with low overpotential and high rate capability. (November 2017) - Gao, Rui; Liang, Xiu; Yin, Penggang; Wang, Junkai; Lee, Yu Lin; Hu, Zhongbo; Liu, Xiangfeng
Abstract: Replacing Li2 O2 with LiO2 as the discharge product is a very promising strategy to tackle the problems of high overpotential (~ 1.5 V), inferior rate capability and short cycle life in the current Li-O2 batteries based on Li2 O2 . But it's very difficult to control LiO2 due to its thermodynamic instability. Herein, we have successfully built a facile rechargeable Li-O2 battery based on the formation and decomposition of amorphous LiO2 with an ultralow overpotential (~ 0.3 V), long cycle life and high rate capability under the catalysis of 3D-architectured Pd-rGO. In-situ Raman spectrum, linear sweep voltammetry, UV–vis measurements and SAED (Selected Area Electron Diffraction) all have identified the amorphous LiO2 -based electrochemical process. Amorphous LiO2 shows a lower oxidation potential and a faster ionic conductivity contributing to the excellent electrochemical performances and the mitigation of undesirable side reactions. This study opens a new horizon to solve the intrinsic problems of the current Li-O2 batteries. Graphical abstract: Highlights: A Li-O2 battery based on amorphous LiO2 has been built for the first time. Amorphous LiO2 has been identified by In-situ Raman spectrum, linear sweep voltammetry and UV–vis measurements. The LiO2 -based Li-O2 battery shows an ultralow overpotential, high rate capability and long cycling stability. A synchronized reduction strategy was proposed to prepare 3D-architectured Pd-rGO catalyst. The side reactions have been mitigated due to the significant decrease of the oxidation potential.